Seizure Occurrence Following Nonoptimal Anticonvulsant Medication Management During the Transition Into the Hospital. (October 2013) - Jones, Charlotte; Kaffka, Jaimee; Missanelli, Megan; Dure, Leon; Ness, Jayne; Funkhouser, Ellen; Kilgore, Meredith; Yu, Feliciano; Safford, Monika M.; Saag, Kenneth
Previous work has shown that medication errors related to anticonvulsants are common during the transition into the hospital for pediatric patients. The purpose of this work was to evaluate whether children with epilepsy admitted for reasons other than epilepsy experience nonoptimal care in anticonvulsant medication management preceding the occurrence of seizures. Using a retrospective cohort of children with epilepsy admitted for reasons other than epilepsy, we created timelines from data in the medical record for the children who experienced seizures. These timelines included the timing and concentration of anticonvulsant administration and seizure occurrence. Three child neurologists independently identified whether nonoptimal care preceded the occurrence of seizures and potentially contributed to the occurrence of the seizure. Of 120 children, 18 experienced seizures and 12 experienced nonoptimal care in anticonvulsant management preceding seizure occurrence. Nonoptimal care that occurred during the transition into the hospital included missed doses of anticonvulsants, delays in administration during which seizures occurred, and patients inadvertently not receiving their home dosing of medication. Anticonvulsant medication errors are known to occur during the transition into the hospital. Here we present a case series of children who experienced nonoptimal care in anticonvulsant medication management who subsequently experienced seizures. Further work to identify how likely the outcome of seizures is following anticonvulsant medication errors, specifically focusing on timing as well as interventions to change the system issues that lead to these errors, is indicated.